Zinc oxide nanoparticles as novel alpha-amylase inhibitors - Dhobale, Sandip; Thite, Trupti; Laware, S. L.; Rode, C. V.; Koppikar, Soumya J.; Ghanekar, Ruchika-Kaul; Kale, Sangeeta N. (Journal of Applied Physics, 2008)
Amylase inhibitors, also known as starch blockers, contain substances that prevent dietary starches from being absorbed by the body via inhibiting breakdown of complex sugars to simpler ones. In this sense, these materials are projected as having potential applications in diabetes control. In this context, we report on zinc oxide nanoparticles as possible alpha-amylase inhibitors. Zinc oxide nanoparticles have been synthesized using soft-chemistry approach and 1-thioglycerol was used as a surfactant to yield polycrystalline nanoparticles of size similar to 18 nm, stabilized in wurtzite structure. Conjugation study and structural characterization have been done using x-ray diffraction technique, Fourier transform infrared spectroscopy, UV-visible spectroscopy, and transmission electron microscopy. Cytotoxicity studies on human fibrosarcoma (HT-1080) and skin carcinoma (A-431) cell lines as well as mouse primary fibroblast cells demonstrate that up to a dose of 20 mu g/ml, ZnO nanoparticles are nontoxic to the cells. We report for the first time the alpha-amylase inhibitory activity of ZnO nanoparticles wherein an optimum dose of 20 mu g/ml was sufficient to exhibit 49% glucose inhibition at neutral pH and 35 degrees C temperature. This inhibitory activity was similar to that obtained with acarbose (a standard alpha-amylase inhibitor), thereby projecting ZnO nanoparticles as novel alpha-amylase inhibitors. (C) 2008 American Institute of Physics. [DOI: 10.1063/1.3009317]

Characterization of biocompatible NiCo2O4 nanoparticles for applications in hyperthermia and drug delivery - Kale, Sangeeta N.; Jadhav, Anil D.; Verma, Seema; Koppikar, Soumya J.; Kaul-Ghanekar, Ruchika; Dhole, Sanjay D.; Ogale, Satishchandra B. (Nanomedicine-Nanotechnology Biology and Medicine, 2012)
Monodispersed, superparamagnetic nickel cobaltite (NCO) nanoparticles were functionalized using mercaptopropionic acid (MPA). MPA conjugates with NCO forming a metal-carboxylate linkage, with the MPA-MPA interaction occurring via formation of disulfide bonds, leaving another carboxyl end free for additional conjugation. The cytotoxicity studies on NCO-MPA show cell viability of similar to 100% up to a dosage of 40 mu g/mL on SiHa, MCF7, and B16F10 cell lines, and on mouse primary fibroblasts. Time-dependent cell viability studies done for a duration of 72 hours showed the cell lines' viability up to 80% for dosages as high as 80 mu g/mL. Negligible leaching (<5 ppm) of ionic Co or Ni was noted into the delivery medium. Upon subjecting the NCO-MPA dispersion (0.1 mg/mL) to radiofrequency absorption, the nanoparticles were heated to 75 degrees C within 2 minutes, suggesting its promise as a magnetic hyperthermia agent. Furthermore, the amino acid lysine and the drug cephalexin were successfully adducted to the NCO system, suggesting its potential for drug delivery. From the Clinical Editor: NCO-MPA nanopartciles were found to be promising magnetic hyperthermia agents, suggesting potential future clinical applications. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cytotoxicity; drug delivery; Magnetic hyperthermia; Magnetic nanoparticles